Kyivan Rus Kolts with enamels and Niello: genesis, sources of inspiration, iconography, attribution issues - Shkolna, Olga V.; Sosik, Olha D.; Barbalat, Oleksandra V.; Sytnyk, Iryna V.; Kashshay, Olena S. (Linguistics and Culture Review, 2021)
Kolts of the Kyivan Rus era is a Ukrainian goldsmiths’ brand, personification of the highest achievements of artistic thought of the then jewelers, behind which you can feel the huge inner spiritual culture of the masters and their professional impeccable knowledge of materials and techniques. At the same time, the ability of Kyivan Rus authors to crystallize their own domestic style is striking. Its special refinement indicates the deep knowledge the local people had of the best creative achievements of the artistic ecumene, awareness of many of the then fashionable trends of jewelry art in Europe and the East. Currently a significant part of the available artifacts from the heritage of jewelers of the Kyivan Rus era requires verification. After all, using a low level of provenance, individual collections announce fake or “modified” or reconstructed kolts to be the real pre-Ukrainian ones. In this regard, the factors of professional art history attribution are extremely important, though they are not widely used in the circles of archeologists, historians, and local history museum specialists.